2015
DOI: 10.5713/ajas.14.0275
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Descriptive Sensory Attributes and Physicochemical Analysis of Broiler and Taiwan Native Chicken Breast Meat

Abstract: Unique organoleptic characteristics such as rich flavors and chewy texture contribute to the higher popularity of native chicken in many Asian areas, while the commercial broilers are well-accepted due to their fast-growing and higher yields of meat. Sensory attributes of foods are often used to evaluate food eating quality and serve as references during the selection of foods. In this study, a three-phase descriptive sensory study was conducted to evaluate the sensory attributes of commercial broiler (BR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 22 publications
5
46
0
Order By: Relevance
“…In our previous study, we demonstrated high negative correlations between the moisture release evaluated by the panelists and percentage of cooking loss of Taiwan native chicken breast meat probably because of the higher water retention of cooked meat (Chumngoen & Tan 2015). In our previous study, we demonstrated high negative correlations between the moisture release evaluated by the panelists and percentage of cooking loss of Taiwan native chicken breast meat probably because of the higher water retention of cooked meat (Chumngoen & Tan 2015).…”
Section: Descriptive Sensory Evaluationmentioning
confidence: 86%
See 4 more Smart Citations
“…In our previous study, we demonstrated high negative correlations between the moisture release evaluated by the panelists and percentage of cooking loss of Taiwan native chicken breast meat probably because of the higher water retention of cooked meat (Chumngoen & Tan 2015). In our previous study, we demonstrated high negative correlations between the moisture release evaluated by the panelists and percentage of cooking loss of Taiwan native chicken breast meat probably because of the higher water retention of cooked meat (Chumngoen & Tan 2015).…”
Section: Descriptive Sensory Evaluationmentioning
confidence: 86%
“…The parameters including cooking time, cooking loss, color and shear force value were determined using 10 breast fillets (n = 10) per time for each cooking method. Shear force was applied perpendicularly to the muscle fiber axis and determined with the operating parameters of a cross-head speed of 4 mm/s and a 10 kg load cell (Chumngoen & Tan 2015) with 40 determinations (40 pieces of samples) per treatment. Meat temperature was monitored at the center of the sample via the thermometer.…”
Section: Physicochemical Analysismentioning
confidence: 99%
See 3 more Smart Citations